Gambaran Umum Kesejahteraan Psikologis Mahasiswa - Epi Kurniasari; Nandang Rusmana; Nandang Budiman (Program Studi Bimbingan dan Konseling Universitas Muhammadiyah Tasikmalaya, 2019)
This study aims to determine the condition of psychological well-being for college studentsin the accounting education study program at Indonesia University of Education. The instrument usedin this research is the scale of psychological well-being. The subjects in this research is 79 collegestudents in the 2018/2019 accounting education study program. The results showed that 38% of collegestudents had low psychological well-being, 46% of college students had medium psychological wellbeing and 16% of the college students had hidgh psychological well-being. The results of this researchcan be used by counselors to improve psychological well-being with guidance or counseling technique.